Kedudukan Surat Pengakuan Utang Dilegalisasi Oleh Notaris Terkait Pembuatan Akta Kuasa Menjual Dalam Hal Terjadi Sengketa di Kota Padang - Agusvia Rahmi Yanti; Warman, Kurnia; Rosari, Anton (Universitas Ekasakti, 2024)
Article 15 paragraph (2) letter a of Law Number 2 of 2014 Amendment to Law Number 30 of 2004 concerning the Position of a Notary that the Notary in his/her position has the authority to ratify signature and determine the exact date of the letter under hand, by registering it in a special book. A debt acknowledgment letter that already contains an element of default and gives rise to legal consequences can be executed with a deed of power of attorney to sell. 1) What is the process for making a debt acknowledgment letter as collateral for a debtor's debt in Padang City? 2) Why does the making of debt acknowledgment letters in Padang City tend to still be done privately and therefore require legalization by a notary? 3) What is the position of a power of attorney to sell that has been legalized by a notary regarding making a power of attorney deed to sell in the event of a dispute in Padang City? By using empirical juridical research methods, this research concludes that the process of legalizing a debt acknowledgment letter in Padang City is that the debt acknowledgment letter must be in the form of a private deed and can be agreed upon by the parties, then the debt acknowledgment letter is signed by the parties and legalized before a notary, the contents of which are the responsibility of both parties in the principle of agreement/consensus, the signing is ratified before a notary, the contents of which are the responsibility of both parties. In the process of legalizing a debt acknowledgment letter, the notary only witnesses the signing of the private letter on the same day, date, month and year at the time of legalization and then provides a legalization number, affixes a stamp/position seal to each page and records it in the private letter reportorium book. confirmed. The reasons debt acknowledgment letters in Padang City tend to still be done privately are: Factors from the community and Factors from the Notary. The position of a debt acknowledgment letter legalized by a notary regarding the making of a power of attorney deed to sell in the event of a dispute in the city of Padang, namely, a debt acknowledgment letter legalized by a notary can be used as evidence in court if a civil case occurs, and the additional guarantee of the sale power deed made before a notary is null and void. law if one of the parties to the agreement dies. As explained in Article 1813 of the Civil Code regarding the end of the grant of power of attorney. However, a power of attorney deed to sell has the same status as a debt acknowledgment letter and can be used as evidence in court.